1989
DOI: 10.1038/bjc.1989.385
|View full text |Cite
|
Sign up to set email alerts
|

A novel hybridoma antibody (PASE/4LJ) to human prostatic acid phosphatase suitable for immunohistochemistry

Abstract: Summary A murine monoclonal antibody PASE/4LJ to prostatic acid phosphatase (PAP) was used to immunostain a wide variety of sections of benign and malignant tissues (654 blocks). Non-neoplastic adult and fetal prostatic glands, primary and metastatic prostatic carcinomas, and scattered cells in prostatic and penile urethra were positive. Rat, dog and rabbit prostates were negative. Nine of 400 tumours of non-prostatic origin showed some positivity: 6/36 carcinoids, 1/9 islet cell tumours, 1/55 ovarian adenocar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
19
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 35 publications
1
19
0
Order By: Relevance
“…In contrast, several studies failed to observe PAP staining in normal tissues, including bladder, breast, colon/rectum, epidermis, kidney, liver, lung, ovary, salivary glands, stomach, testes, and urethra [11,12,15,16]. Using qPCR to measure relative levels of PAP mRNA transcripts, Cunha and colleagues [14] found that, relative to prostate, PAP mRNA was expressed at low levels in several normal tissues, most notably in placenta, kidney, and testis.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…In contrast, several studies failed to observe PAP staining in normal tissues, including bladder, breast, colon/rectum, epidermis, kidney, liver, lung, ovary, salivary glands, stomach, testes, and urethra [11,12,15,16]. Using qPCR to measure relative levels of PAP mRNA transcripts, Cunha and colleagues [14] found that, relative to prostate, PAP mRNA was expressed at low levels in several normal tissues, most notably in placenta, kidney, and testis.…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, Cohen et al found weak diffuse PAP immunostaining in islets cells, but concluded the weak PAP signal was non-specific [21]. Additional studies have found PAP expressed in normal pancreatic tissue [11,12,18].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations